Pengaruh opini audit tahun sebelumnya, kondisi keuangan dan auditor client tenure terhadap opini audit going concern dengan ukuran perusahaan sebagai variabel kontrol (Studi empiris pada Perusahaan Automotive and Components yang terdaftar di BEI - Bernandus Hutajulu; Restu Agusti; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of audit opinion prior year, financial condition, auditor client tenure on going concern audit opinion with firm size as a control variable. Its population is a automotive and components company registered in Indonesian Stock Exchange in 2010-2012. There is 16 companies in the sample with purposive sampling technique. The Method of analysis used in this study is logistic regression with sofware SPSS (Statistical Product and Service Solution) support. The examine of data used in this study for logistic regression is examine overall model fit and hypothesis. The results of the tests performed in this study shows that the audit opinion prior year, financial condition, auditor client tenure and firm size does not significantly influence going concern audit opinion. This suggests that many other factors that affect the going concern audit opinion. Keywords : Audit Opinion Prior Year, Financial Condition, Auditor Client Tenure, Firm Size, Going Concern Audit Opinion.